Adherence to antiretroviral drugs: self-reported of missed doses and associated factors in people living with HIV - Lotufo Estevam, Denize; Gianna Luppi, Carla; Aparecida da Silva, Maria; Olhovetchi Kalichman, Artur; Bivanco-Lima, Danielle; Queiroz Rocha, Simone (Brazilian Journal of Sexually Transmitted Diseases, 2024)
Introduction: AIDS has become a chronic disease that may not be sexually transmitted as long as people living with HIV take their medications correctly. Therefore, adherence to antiretroviral drugs remains a central issue for therapeutic success. Objective: To describe the prevalence of self-reported missed doses of antiretroviral drugs (MDARV) in people living with HIV and analyze its associated factors. Methods: A cross-sectional study was conducted in a specialized service on STI/HIV/AIDS in the city of São Paulo (SP), Brazil. The data sources used were a self-administered form and the Database of the Laboratory Test Control System of the National Network for CD4+/CD8+ Lymphocyte Count and HIV Viral Load. The dependent variable was the self-report of MDARV by users in the last three days. The independent variables were related to sociodemographic, behavioral, and healthcare-associated characteristics. Poisson regression was used to estimate prevalence ratios and 95% confidence intervals. Results: Among the 510 responding participants, the MDARV prevalence in the last three days was 15.9% (95%CI 12.69–19.06). Factors associated with MDARV were detectable viral load, practicing a religion, change of residence in the last year, use of drugs, and more than 11 years of treatment. Knowing CD4+ T lymphocyte count was associated with protection regarding missed doses. Conclusion: Monitoring MDARV self-report is a simple tool that can improve comprehensive care for people living with HIV/AIDS.